Towards an Integrated Waterway Transport System in the Danube Region - Szabolcs Simon (Journal of Economics and Management, 2015)
The global economic power shift from West to East requires new techniques in spatial development of East Central Europe. This paper aims to examine what challenges and opportunities this process can pose for the Danube Region, how integrated infrastructure planning and sustainable, resource-efficient transportation can contribute to prosperity, emphasizing that international and global environmental issues that affect infrastructural development should be considered for regional strategies and transnational cooperation.